Characterizing design thinking towards integration with product-service system development process - Rosa, Maiara (2017)
Many companies have been trying to shift their business core from offering products to offer product-service systems (PSS), what requires not only a shift in the business model, but also in the culture and mindset. Using user-centered methods to support the PSS development process is a way to support this shift and to enhance perceived value of PSS offerings. One possible approach to support PSS development on becoming more user-centered is design thinking (DT). It is a user-centric approach used by many leader enterprises to support innovation and described by several methodologies with practical focus. However, it is not clear in literature how to integrate DT and development process models already used by companies, leading to cases where practitioners may replace complete phases, or even the whole development process, by DT. This replacement does not seem appropriate, since DT may lack aspects that are considered by PSS development processes. The main objective of this work is to identify how the DT approach can be applied in PSS development processes. The methodology of this research combines the following methods: case research, corpus linguistics, frame semantics and matrix-based methods. One of the results of this work is the characterization of DT based on the linguistic analysis, which was derived from content extracted from more than 1500 pages of 8 DT methodologies. This analysis resulted in 46 recurrent activities, associated with 458 specific guidelines, and the identification of 182 relevant activities that synthetize the DT methodologies. Those activities were compared to 14 PSS development process models from literature, concluding, among other findings, that DT cannot replace the PSS design process models, and that the compatibility for integration of DT into PSS development process models is greater on the front-end of innovation (FEI). FEI activities from 14 PSS and 7 product development process models were compared with DT recurrent and relevant activities to provide understanding on how DT can be integrated into PSS development process models. Finally, the findings of this last comparison led to the creation of a 4-step method for integrating DT into PSS development process models based on activities similarity.